Two Stay Two Stray Type Cooperative Learning Model on The Learning Outcomes of IPS Class V SD Students of Negeri 125138 Pematang Siantar - Necia Sitorus; Lisbet Novianti Sihombing; Osco Parmonangan Sijabat (International Journal of Integrated Science and Technology, 2023)
The background to this research is based on observations made by researchers in class V of SD Negeri 125138 Pematang Siantar, namely that teachers still use conventional learning models so that students are less involved in the learning process. This makes the learning process less than optimal and student learning outcomes have not been achieved in accordance with the Minimum Completeness Criteria. From this problem, it is necessary to find a solution, namely by implementing the Two Stay Two Stray type cooperative learning model . This learning model is suitable to be applied to social studies subjects because this learning model invites students to communicate, work together and be responsible in groups because they have their own tasks. This learning model can improve the quality of social studies learning so that students are more active, creative and learning is more meaningful so that learning outcomes can improve. This research used a pre-experimental method with a One Group Design Pretest-Posttest design with a sample of 38 students. Based on the results of the data analysis tests carried out, the Hypothesis Test results were obtained, t = 15,371 and t table = 2,026 with t count > t table = 15,371 > 2,026, so H 0 was rejected and Ha a was accepted. With this explanation, it can be concluded that there is an influence of the Two Stay Two Stray type cooperative learning model on the social studies learning outcomes of class V students at SD Negeri 125138 Pematang Siantar.